Evaluation of the Spinoffs Criteria: A Lesson from The Indonesian Islamic Banking Industry - M Nur Rianto Al Arif; Nachrowi D Nachrowi; Mustafa Edwin Nasution; T.M. Zakir Mahmud (Ekonomi Syariah IAIN Kudus, 2018)
Spin-off policy is one of the crucial issues in the Indonesian Islamic Banking Act (The Act of 21/2008). This paper is going to evaluate the spinoffs criteria that are inherent in the Act of 21/2008. The method that has been used in this paper to evaluate the spinoffs criteria is ARIMA and simulation. This ARIMA method is used to forecast that the Islamic banking unit can achieve the fifty percent asset after fifteen years after this act. The object that is used in this paper is four Islamic spin-off's banks, five Islamic banking units, and two Islamic full-fledged banks. The ARIMA result shows that from all of the objects in fifteen years or the year of 2023, there are no Islamic banks either Islamic full-fledged banks or Islamic banking unit can achieve the fifty percent asset. Besides that, based on the simulation it needs high growth asset to achieve the market share asset of its parent’s banks. According to these results, this study suggests the regulator should revise the spinoffs criteria using the strict criteria that based on either nominal assets, capital, financial ratio or the others.